The Effect of Local Culture, Institutional Organizational Culture on Employee Performance and Customer Satisfaction with Services - Rahmaddian Rahmaddian; Deni Surapto; Stefani Made Ayu A. K. (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
In this millennial era competition, there are many innovations to ensure the sustainability of a sustainable life in providing services to consumers, both products and services as expected by consumers. Therefore, it is necessary to have the quality of human resource performance to respond competitively in gaining market share. The success of high-performing employees is strongly influenced by innovative HR performance and organizational commitment and organizational citizenship behavior [Zhang, 2014]. To analyze local culture on organizational culture, to analyze organizational culture on organizational performance, to analyze employee performance on customer satisfaction with services. The method used in this research was quantitative descriptive strengthened by qualitative descriptive. The population of this study was all staffs of UPBJJ-UT. The sample and interview process were UPBJJ-UT which had local cultural characteristics. (Javanese Culture, UPBJJ-UT Yogyakarta, Sumatran Culture UPBJJ-UT Jambi / Pekanbaru, Timor Culture UPBJJ-UT Jayapura. The next analysis using the Hypothesis Tutorial in this study utilized the Partial Least Square (PLS) method. PLS is an alternative method of analysis with variance-based Structural Equation Modeling (SEM). The findings in this study are many other organizations formed in the local UPBJJ-UT, local culture and the dominant organizational culture of the company is work culture; although the culture has been formed and influenced by leaders and newcomers in influencing the existing work culture to support service satisfaction, because the nature of distance higher education is independence. According to this research, institutions need to re-evaluate their cultural values and try to communicate about local culture and organizational culture; In addition, the researcher also found that UPBJJ-UT staffs preferred local culture that had been applied to the organizational culture for the island of Java, the majority of which held tightly to Eastern culture, while samples in the eastern regions where the average employees were natively from other provinces and more dominant than local human resources.